1989
DOI: 10.2105/ajph.79.9.1243
|View full text |Cite
|
Sign up to set email alerts
|

Maternal smoking during pregnancy: no association with congenital malformations in Missouri 1980-83.

Abstract: Using a multisource birth defects registry developed by the Missouri Center for Health Statistics for the years 1980-83, we examined the relation between maternal smoking during pregnancy and the occurrence of congenital malformations. There were 288,067 live singleton births in this data set of which 10,223 had one or more congenital malformations. When adjusted for potential confounders the odds ratio for congenital malformations in the infants of women

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 22 publications
3
27
0
1
Order By: Relevance
“…Two early studies of clubfoot did not report any association between clubfoot and maternal smoking. 10,14 No association was observed between maternal smoking and congenital diaphragmatic hernia, which is consistent with the one literature report located. 14 We also did not observe an association between maternal smoking and Down syndrome, although two literature reports have shown a possible protective effect of maternal smoking on Down syndrome 14,27 and one other report showed a protective effect among heavy smoking primiparas.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Two early studies of clubfoot did not report any association between clubfoot and maternal smoking. 10,14 No association was observed between maternal smoking and congenital diaphragmatic hernia, which is consistent with the one literature report located. 14 We also did not observe an association between maternal smoking and Down syndrome, although two literature reports have shown a possible protective effect of maternal smoking on Down syndrome 14,27 and one other report showed a protective effect among heavy smoking primiparas.…”
Section: Discussionsupporting
confidence: 91%
“…[9][10][11][12] Although some early small studies showed an increased risk of neural tube defects associated with maternal smoking, 13 this finding has not been supported by more recent studies. Pregnancies affected by either anencephaly or spina bifida have high rates of spontaneous abortion, and the likelihood of spontaneous abortion of affected fetuses may be increased among women who smoke.…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of these factors on a population in causing birth defects (except in specific circumstances) is far from certain. While smoking has been associated with low birth weight and alcohol is correlated with fetal alcohol syndrome, there is little consistent evidence in the literature (41)(42)(43) to suggest an association with other congenital malformations.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoking during pregnancy was associated with cleft defects [6,99,110]. In contrast, some studies found no association with maternal smoking for any form oral clefts [111,112]. Meta-analysis of 24 case-control and cohort studies revealed significant association with an overall odds ratio of 1.34 (95% CI= 1.25-1.44) [113].…”
Section: Environmental Factors Causing Cleftmentioning
confidence: 99%